A Comprehensive Assessment of Natural Fractures in the Mishrif Formation: Slide Studies, Core Samplings, Borehole Imaging, and Logging Techniques - Al-mohsen, Noor Al-huda Q.; Handhal, Amna M. (Iraqi Journal of Science, 2025)
The Mishrif Formation in the Rumaila oilfield is a prolific carbonate reservoir with significant hydrocarbon production. However, the role of natural fractures in enhancing reservoir characteristics remains poorly understood. This study aims to characterize and identify naturally occurring fractures within the Mishrif Formation using a multi-methodological approach integrating core and thin section analysis, borehole image logs, and conventional well logs. Results indicate different types of natural fractures, such as open, filled, vuggy, and propped fractures. The open type dominates the field; thus, the potential for oil production from this formation is high. Fracture orientation analysis revealed that the N-W and S-E directions have the largest percentage of fractures, making these areas favorable for drilling more wells. The main conclusion of this research is that the use of integrated methods enables the characterization and quantification of natural fractures, significantly contributing to the efficient management of oil reservoir units.